2017
DOI: 10.1007/s00125-017-4215-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined NOX1/4 inhibition with GKT137831 in mice provides dose-dependent reno- and atheroprotection even in established micro- and macrovascular disease

Abstract: Aims/hypothesis Oxidative stress is a promising target in diabetes-associated vasculopathies, with inhibitors of NADPH oxidases (NOX), in particular isoforms 1 and 4, shown to be safe in early clinical development. We have explored a highly relevant late-stage intervention protocol using the clinically most advanced compound, the NOX1/4 inhibitor GKT137831, to determine whether end-organ damage can be reversed/attenuated when GKT137831 is administered in the setting of established diabetic complications. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 36 publications
7
69
0
Order By: Relevance
“…In the vasculature, Nox 1 is upregulated in diabetes and Nox 1 KO mice develop less atherosclerosis in the diabetes setting (41). Furthermore, GKT137831, an inhibitor of both the Nox 1 and Nox 4 isoforms, has been demonstrated to prevent atherosclerosis in diabetic apoE 2/2 mice (41) and more recently was shown in a delayed intervention model to confer vascular benefits, including reduced plaque accumulation and less vascular inflammation in diabetic mice with established atherosclerosis (42). As this pharmacological approach inhibits not only Nox1 but also Nox 4, it was difficult to determine the specific mode of action of this drug.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In the vasculature, Nox 1 is upregulated in diabetes and Nox 1 KO mice develop less atherosclerosis in the diabetes setting (41). Furthermore, GKT137831, an inhibitor of both the Nox 1 and Nox 4 isoforms, has been demonstrated to prevent atherosclerosis in diabetic apoE 2/2 mice (41) and more recently was shown in a delayed intervention model to confer vascular benefits, including reduced plaque accumulation and less vascular inflammation in diabetic mice with established atherosclerosis (42). As this pharmacological approach inhibits not only Nox1 but also Nox 4, it was difficult to determine the specific mode of action of this drug.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In metabolically compromised animals, oxidant stress is thought to be an important link between glucose disturbances and impaired function of the kidney. Several reports have described a causal role for NOX4 in renal dysfunction that can lead to hypertension 50, 51. In salt‐sensitive rats, urinary hydrogen peroxide has been shown to be elevated with increased renal perfusion pressure, and deletion of renal NOX4 attenuates hypertension 52, 53, 54.…”
Section: Discussionmentioning
confidence: 99%
“…The main sources of superoxide in the kidney are the NOX enzymes, specifically the homologs NOX4 and NOX5, the latter only present in humans 63. Many factors that are upregulated in diabetes affect the expression and activity of these enzymes including glucose and the RAAS resulting in increases in pro‐inflammatory and pro‐fibrotic markers including the NFκB p65 subunit, transforming growth factor beta (TGF‐β), tumor necrosis factor alpha (TNF‐α) and fibronectin 64. The current treatments for DN include glucose control and RAAS blockade; however, these treatments only slow the progression of the disease, rather than improving DN and patient outcome.…”
Section: Diabetic Nephropathy Antioxidant Defences and Immunotherapiesmentioning
confidence: 99%
“…Recent studies have examined the use of a dual NOX1/NOX4 inhibitor (GKT137831) to prevent the development of DN65 in both early and delayed interventional T1D mouse models 64. These studies showed that inhibiting NOX1/NOX4 confers renoprotection by decreasing albuminuria, ROS production and glomerular macrophage infiltration 64, 65.…”
Section: Diabetic Nephropathy Antioxidant Defences and Immunotherapiesmentioning
confidence: 99%